RUA, ATMOSFERA E LUGAR - Fiori, Isabela Maria; Singeski, Luiz Gustavo Grochoski; Schmid, Aloísio Leoni; Rossi, Francine a (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Streets represents most of the public space of a city and, as such, is an element of great importance in the construction of this. It s in the design of cities, thought in "relation to" and "to" human beings, that the greatest and most significant contributions to a more environmentally, socially and economically sustainable society can be made. This paper seeks to understand, through bibliographical analysis, how the conception of the streets as a system of free public spaces focused in the experience of the pedestrian / citizen and provided with a phenomenologically measurable atmosphere can collaborate in the development of better and more sustainable cities.